Nanoporous materials IV : proceedings of the 4th international symposium on nanoporous materials, Niagara Falls, Ontario, Canada June 7-10 2005 - Sayari, A. (Abdelhamid); Jaroniec, M. (Studies in surface science and catalysis, 2005)
Nanoporous Materials IV contains the invited lectures and peer-reviewed oral and poster contributions to be presented at the 4th International Symposium on Nanoporous Materials, which will be hosted in Niagara Falls, Ontario, Canada, June 7-10, 2005. This volume covers complementary approaches to and recent advances in the field of nanostructured materials with pore sizes larger than 1nm, such as periodic mesoporous molecular sieves (e.g., MCM-41 and SBA-15) and related materials including clays, ordered mesoporous carbons, colloidal crystal templated materials, porous polymers and sol gels. The broad range of topics covered in relation to the synthesis and characterization of ordered mesoporous materials are of great importance for advanced adsorption, catalytic, separation and environmental processes as well as for the development of nanotechnology. This volume contains over 120 contributions related to the synthesis of ordered mesoporous silicas, organosilicas, nonsiliceous inorganic materials, carbons, polymers and related materials, their characterization and applications in adsorption, catalysis and environmental clean up. * Unique contributions brings readers up-to-date on new research and application developments * Figures and tables supplement comprehensive topics * Extensive author and subject index.